PROSPECTS OF DIGITAL PUBLISHING IN THE PUBLISHING HOUSE OF THE LITHUANIAN LANGUAGE INSTITUTE - KISIELIŪTĖ, RIMANTĖ (Knygotyra, 2010)
The article presents the situation and prospects of digital publishing in an academic publishing house. Based on the analysis of a quantitative survey, interviews and nonfiction, the article presents the opinion of the Lithuanian Language Institute researchers (present and future book authors) about digital publishing and the reasons why digital publishing is useful in an academic publishing house; finally, it explores three publishing models (born-digital, print on demand, short run digital publishing) which are useful in expanding production volumes in a publishing house.The research has lead to the conclusion that digital publishing has all preconditions to be rapidly developed while seeking economical advantages, risk minimization, and convenience.
Keywords: ...